2022
DOI: 10.3389/fnut.2022.1030385
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antidiabetic activities of a polyphenol rich extract obtained from Abelmoschus esculentus (okra) seeds using optimized conditions in microwave-assisted extraction (MAE)

Abstract: Functional foods have gained popularity in recent decades. They are exploited for their bioactive compounds like polyphenols, which are highly demanded in cosmetic, pharmaceutical and nutraceutical industries. However, extractive techniques and conditions used up to recently are almost obsolete and must be optimized for higher efficiency. The current study aimed to evaluate the antidiabetic potential of an optimized extract of Abelmoschus esculentus (okra) seeds. The optimal conditions for extracting polypheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…These two peaks were typical of how carbohydrates were absorbed. As confirmed by Alba et al 50 and Woumbo et al , 14 the peaks at 1620 cm −1 , 1720 cm −1 and 1030 cm −1 suggest that the polysaccharide may include stretching vibration of free and methyl-esterified carboxyl and glycosidic groups, respectively. The peak at 820 cm −1 refers to the α-configuration in the polysaccharide, according to Zhang et al 51 The peaks between 1152 and 995 cm −1 indicate the presence of arabinoxylan in okra mucilage, as reported by Wang et al 19 The FTIR findings shown above are consistent with those of earlier investigations.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…These two peaks were typical of how carbohydrates were absorbed. As confirmed by Alba et al 50 and Woumbo et al , 14 the peaks at 1620 cm −1 , 1720 cm −1 and 1030 cm −1 suggest that the polysaccharide may include stretching vibration of free and methyl-esterified carboxyl and glycosidic groups, respectively. The peak at 820 cm −1 refers to the α-configuration in the polysaccharide, according to Zhang et al 51 The peaks between 1152 and 995 cm −1 indicate the presence of arabinoxylan in okra mucilage, as reported by Wang et al 19 The FTIR findings shown above are consistent with those of earlier investigations.…”
Section: Resultsmentioning
confidence: 60%
“…The peak at 820 cm −1 refers to the α-configuration in the polysaccharide, according to Zhang et al 51 The peaks between 1152 and 995 cm −1 indicate the presence of arabinoxylan in okra mucilage, as reported by Wang et al 19 The FTIR findings shown above are consistent with those of earlier investigations. 14,52 3.4. Scanning electron microscope of okra mucilage and flesh Fig.…”
Section: Ftir Spectrometric Analysis Of Okra Mucilagementioning
confidence: 99%
See 1 more Smart Citation
“…Sonic treatment, either by immersion in a sonic water bath or using horn and probe devices, is used to increase the rate of extraction for granular solids and to disrupt the cellular structure of biological samples. Sonic water baths allow samples to be batched and processed in parallel, but the extraction efficiency may depend on the location of the (ii) Microwave-assisted solvent extraction Okra seeds Polyphenols P = 330 W, t = 9.5 min, sample/solvent = 0.01, ethanol-water (1:1), particle size < 0.5 mm (domestic microwave oven) [45].…”
Section: Uase and Microwave-assisted Solvent Extractionmentioning
confidence: 99%
“…Capital costs for closed vessel systems are high compared with traditional extraction methods. Applications for HPTLC analysis are limited so far to botanicals and are summarized in Table 3 [2123, 45, 46]. In most cases, open vessels using domestic microwave ovens were used, which fail to take full advantage of the possibilities of MASE.…”
Section: Solvent Extraction (Solids)mentioning
confidence: 99%